Hubungan antara Kecerdasan Emosional dengan Kontrol Diri dalam Penggunaan Media Sosial pada Generasi Z - Azizah Nur Auliya; Winarsih, Tri (Universitas Darul Ulum, 2025)
Generation Z is a generation that grew up with the rapid growth of technology. The rapid development of technology can have a negative impact on Generation Z if not accompanied by good self-control. One example is the rise of negative comments on social media or what can also be called cyberbullying. This is the basis for this research, to find out the relationship between emotional intelligence and self-control in the use of social media in generation z. Product moment correlation is a data analysis technique used in this study with the method used is quantitative. The number of respondents in this study was 101 people with criteria aged 12-26 years (Generation Z) in Yogyakarta and regularly use social media. The results of this study are that the categorization carried out obtained results in the form of moderate self-control variables and high emotional intelligence variables. The results of the hypothesis are accepted, in which there is a positive relationship between emotional intelligence variables and self-control in the use of social media in Generation Z in Yogyakarta.